Consider “HACKS” when designing hackathon challenges: Hook, action, collaborative knowledge sharing - Wallwey, Cassie; Longmeier, Meris M.; Hayde, Donnelley; Armstrong, Julia; Kajfez, Rachel; Pelan, Renee (Frontiers in Education, 2022)
Our world’s complex challenges increase the need for those entering STEAM (Science, Technology, Engineering, Arts, and Math) disciplines to be able to creatively approach and collaboratively address wicked problems – complex problems with no “right” answer that span disciplines. Hackathons are environments that leverage problem-based learning practices so student teams can solve problems creatively and collaboratively by developing a solution to given challenges using engineering and computer science knowledge, skills, and abilities. The purpose of this paper is to offer a framework for interdisciplinary hackathon challenge development, as well as provide resources to aid interdisciplinary teams in better understanding the context and needs of a hackathon to evaluate and refine hackathon challenges. Three cohorts of interdisciplinary STEAM researchers were observed and interviewed as they collaboratively created a hackathon challenge incorporating all cohort-member disciplines for an online high school hackathon. The observation data and interview transcripts were analyzed using thematic analysis to distill the processes cohorts underwent and resources that were necessary for successfully creating a hackathon challenge. Through this research we found that the cohorts worked through four sequential stages as they collaborated to create a hackathon challenge. We detail the stages and offer them as a framework for future teams who seek to develop an interdisciplinary hackathon challenge. Additionally, we found that all cohorts lacked the knowledge and experience with hackathons to make fully informed decisions related to the challenge’s topic, scope, outcomes, etc. In response, this manuscript offers five hackathon quality considerations and three guiding principles for challenge developers to best meet the needs and goals of hackathon sponsors and participants.